2019
DOI: 10.1007/s42452-019-0530-4
|View full text |Cite
|
Sign up to set email alerts
|

Al–CNT–Ni composite with significantly increased strength and hardness

Abstract: In this study, aluminium-carbon nanotube-nickel (Al-CNT-Ni) composite was prepared by powder metallurgy from pure Al powder and Ni-encapsulated CNT. Previously, carbon nanotubes were coated with nickel following ultraviolet-assisted electroless deposition method. Tensile strength and hardness of the composites were found to increase in proportion to the CNTs addition. For an addition of 7 wt.% Ni-coated CNTs containing 2.5 wt.% nanotubes of 8-15 nm diameter (Ni to CNT ratio was 1-0.357), resultant tensile and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…However, weight reduction of structural materials by light metals often leads to decrease in strength, which causes problems in terms of safety and sustainability. 1,2 The application of magnesium and its alloys has been widespread in aerospace and automobile industries because of their low density, high specific strength and specific stiffness. However, their relatively low absolute strength and stiffness limit their further development, which can be overcome by strengthening using reinforcements, including ceramic and metallic fibers, particles, and carbon fibers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, weight reduction of structural materials by light metals often leads to decrease in strength, which causes problems in terms of safety and sustainability. 1,2 The application of magnesium and its alloys has been widespread in aerospace and automobile industries because of their low density, high specific strength and specific stiffness. However, their relatively low absolute strength and stiffness limit their further development, which can be overcome by strengthening using reinforcements, including ceramic and metallic fibers, particles, and carbon fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, difficulty in the processing is represented by the uniform dispersion of CNT in Mg matrix without any damage of the nanotubes. [22][23][24][25][26] In addition, it has been reported that there are two main challenging issues attributed to the fabrication of Mg matrix composites, which consists of: (1) Extensive oxidation and explosive behavior of Mg. (2) The high reaction tendency with other components during fabrication processes. Lots of researches have been conducted to overcome these challenges by focusing on providing a protective surface to prevent oxidation behavior and processes including reaction elimination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, in order to cope with environmental issues such as CO 2 emissions reduction, replacing various structural materials like heavy metals such as iron (Fe) materials, comprising the major parts in automobiles, buildings, bridges, etc., with light metals such as aluminum (Al), magnesium (Mg), and titanium (Ti) has been highly desirable. However, the weight reduction of structural materials by light metals often leads to a decrease in strength, which causes problems related to safety and sustainability [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the number of carbon layers, CNTs can be classified into two categories: single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs). Due to these interesting properties, CNTs can play a significant role in the fields of nanotechnology, electronics, optics, and materials science [2][3][4]. CNTs have been regarded as a powerful candidate for the reinforcement of metal matrix composites (MMCs) [5,6].…”
Section: Introductionmentioning
confidence: 99%